Do ankle braces affect functional performance? A randomised double-blinded cross-over trial - Tomas Megalaa; Paul L. Le; Alycia Fong Yan; Paula R. Beckenkamp; Claire E. Hiller (JSAMS Plus)
Objectives: To compare the effects of the KISS ankle brace, Aircast ankle brace, and no brace condition, on functional performance measures and perceptions of stability, confidence and reassurance in people with and without chronic ankle instability. Design: Randomised double-blinded cross-over trial. Method: A total of 42 participants (21 uninjured and 21 with chronic ankle instability) were recruited from the general population and completed a series of functional performance tests, including side hop (seconds), Star excursion balance test reach distance, triple hop for distance (centimetres), modified T-agility test (seconds), standing and maximum vertical jump reach (centimetres), while wearing two ankle brace conditions and no brace (control). Results were recorded and analysed by a blinded investigator. Results: There was no significant difference between conditions for average time on the side hop test (F(2,122) ​= ​0.04, P ​= ​0.96); best reach distance on SEBT in anterior (F (2,122) ​= ​0.04, P ​= ​0.96), postero-medial (F(2,122) ​= ​0.08, P ​= ​0.93) and postero-lateral (F(2,122) ​= ​0.08, P ​= ​0.92) directions; best distance performed on the triple hop (F(2,122) ​= ​0.03, P ​= ​0.97); best standing vertical jump performance (F(2,110) ​= ​0.04, P ​= ​0.97); best maximum vertical jump performance (F(2,110) ​= ​0.01, P ​= ​0.99); or best time for the modified T-agility run (F(2,122) ​= ​1.61, P ​= ​0.21). Conclusions: Practitioners can be assured that functional and balance performances will not be impacted by wearing an ankle brace.